The impact of Iran Central Bank's sanction on Tehran Stock Exchange. Issue 3 (8th May 2017) - Salehi, Mahdi; Karimzadeh, Mostafa; Paydarmanesh, Navid
Abstract : Purpose: US sanctions have been a major feature of US Iran policy since Iran's 1979 Islamic revolution, but the imposition of UN and worldwide bilateral sanctions on Iran that began in 2006 and increased dramatically as of 2010 is recent by comparison. The objectives of US sanctions have evolved over time. Broad international sanctions imposed on Iran harmed Iran's economy and contributed to Iran's acceptance of agreements that exchange constraints on its nuclear program for sanctions relief. The subject of this study is important because both Iran and the international communities are demanding for information about the effect of sanctions on Iran. In an international and regional perspective, it seems that sanctions have a negative impact on economic, social and even political status of Iran. Therefore, this paper aims to examine the impact of Iran Central Bank sanction on Tehran Stock Exchange as on December 31, 2011. Design/methodology/approach: Variables of model are consisted by exchange rate, oil prices and Tehran Stock Exchange Price Index (TEPIX) from October 2, 2011 to March 29, 2012, which is offered daily. To analyze the model, the authors used Johansen–Juselius and Autoregressive Distributed Lag (ARDL) methods. Findings: The results indicate that there is a long-run equilibrium relationship between selected variables as oil prices, and exchange rates have a positive effect on the TEPIX. In other words, the results of the econometric estimation show the positive effect of the Iran Central Bank sanction on the TEPIX. Thus, because of economic sanctions imposed by the Western countries, Tehran Stock Exchange has been growing. Originality/value: No empirical research exists that examines the impact of sanctions on stock price in developing countries. This study fills this gap by examining the links between sanctions and stock price in Iran.